Physico-chemical and Microbiological Characterisation of Pheasant and Salted Fish (Lanhouin) Produced and Sold in Lomé - Dossou, Reine Bayi; Atakora, Magnou-Léléng; Mélila, Mamatchi; Soncy, Kouassi; Kangni-Dossou, Mensah; Karou, Damintoti Simpliste; Améyapoh, Yaovi; Gbéassor, Messanvi (Asian Journal of Biological and Life Sciences)
Aim: To assess the quality of Lanhouin produced and sold in Lomé, physico-chemical and microbiological characterisations were carried out on this commodity. Materials and Methods: 45 samples of pheasant and salted fish obtained from the species Pseudotolithus senegalensis, Balistes capriscus, Scomberomus tritor, Decacttylus galéides, Cheilopognon nigricans were collected at Katanga and at the Kodomé market. The standardised routine methods described by the Association Française de Normalisation were used to search for the suspected germs. Physico-chemical analyses were carried out on 10 of the 45 samples taken and concerned water content, fat and protein levels obtained by the AOAC methods. Results: The results showed that samples have water contents ranging from 51% to 65.85% and fat contents from 1.24% to 2.53%. Protein content varied from 33.41% to 53.69%. Microbiological analyses revealed the absence of salmonella. Hygienic quality of the samples analysed was unsatisfactory at 24.44% in relation to total mesophilic flora, at 88.89% in relation to total coliforms, at 33.33% in relation to Escherichia coli, at 62.22% and 8.89% respectively in relation to Sulphite Reducing Anaerobes and Staphylococcus aureus. Yeasts and moulds were found in all the samples collected, which indicates a potential risk of altering the hygienic and marketable qualities of the products. The presence of lactic acid bacteria found in the Lanhouin could result in the possible presence of biogenic amines. Conclusion: These results imply the need to rigorously apply good manufacturing and hygienic practices in order to improve the sanitary quality of pheasant and salted fish for the well-being of its consumers
Keywords: Lanhouin; Lomé; Microbiology; Physico-chemical; Quality